2022
DOI: 10.21203/rs.3.rs-1801171/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico simulations and functional cell studies evidence similar potency and distinct binding of Pacific and Caribbean ciguatoxins

Abstract: Ciguatoxins (CTX) cause ciguatera fish poisoning, which is the most common reported hu-man food poisoning related to natural marine toxins. Pacific ciguatoxins are the most abundant and studied CTX analogues, however, the growing distribution of Caribbean analogues and the limited data available on their biological effects makes necessary to re-evaluate their relative potency. For decades, the guidelines established by regulatory agencies have assumed that the potency of the Caribbean CTXs were 10-fold lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…The combined effects of both food contaminants on sodium channel functionality have not been previously studied. CTXs decreased the maximum peak inward sodium currents at very low concentrations and cause a negative change in the activation voltage of up to 20 mV of VGSC, which is in accordance to previous reports 7,11,17 and also their fast inactivation state. 35,38 BTXs also caused an important negative displacement in the activation voltage of sodium channels of up to 13 mV not modifying the maximum I Na 4,5 and hyperpolarizing their fast inactivation voltage.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The combined effects of both food contaminants on sodium channel functionality have not been previously studied. CTXs decreased the maximum peak inward sodium currents at very low concentrations and cause a negative change in the activation voltage of up to 20 mV of VGSC, which is in accordance to previous reports 7,11,17 and also their fast inactivation state. 35,38 BTXs also caused an important negative displacement in the activation voltage of sodium channels of up to 13 mV not modifying the maximum I Na 4,5 and hyperpolarizing their fast inactivation voltage.…”
Section: Discussionsupporting
confidence: 92%
“…3 However, despite being similar in their mechanism of action, there are differences in the reported effects and potency between the two groups of toxins that indicate that BTXs act at micromolar concentrations, while CTXs present physiological effects at nanomolar concentrations. 4,5 CTXs and BTXs bind to a common site of the sodium channel located at the cleft created by segment S5 of domain IV, segment S6 of domain I, and the P-loop (P1) that connects segments S5 and S6 of domain IV of the VGSC α-subunit 6,7 but with different affinities. Previous studies indicated that CTXs interact specifically and with higher affinity with sodium channels; 8,9 however, the differences in the chemical structures between the CTX analogues generate modifications in their binding and activity over VGSC.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations